The Influence of Independent Commissioners, Institutional Ownership, Audit Committee, and Leverage on the Integrity of Financial Reports in Regional Development Banks - Ariyani, Lisa; Safelia, Nela; Olimsar, Fredy (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the effect of independent commissioners, institutional ownership, audit committees, and leverage on the integrity of financial statements at regional development banks in the Sumatra region registered with the Financial Services Authority. Sampling using purposive sampling. The number of samples in this study was 32, which came from 10 provinces and 2 provinces that were members of other provincial BPDs that published audited annual reports during the 2019-2022 period. The analysis method in this study used multiple linear regression processed using SPSS 29 Software. The results of this study indicate that independent commissioners, institutional ownership and leverage do not affect the integrity of financial statements, while the audit committee has a positive and significant effect on the integrity of financial statements.